Miss Marple - desenvolvimento de ferramenta para auxiliar na verificação e detecção de indícios de plágio com base no método DIP detector de indícios de plágio - Arenhardt, Catiane Priscila Barbosa (2013)
The work aimed to identify the needs that still permeated the tools of analysis and detect plagiarism for further development of a new tool, called Miss Marple, which met the requirements identified in the course of research, besides continuing the work called DIP - Evidence of Plagiarism Detector. The research conducted in this work allowed the survey of the characteristics of each tool enabling trace a comparative study between them and the development of the new tool. The validation of the developed tool was performed in two modes of travel, and distance, and by evaluating the usability of the tool. The results showed that Miss Marple tool, developed, presented good results in the analysis of percentage signs of plagiarism coming to an accuracy of approximately 100% and got the best processing time when compared with three of the tools that were studied (Sniffer plagiarism, Plagius detector and VIPER). In addition to the processing time and consistency analysis of evidence of plagiarism, another factor that deserves mention is the construction of the repository file submitted for analysis, which provides the user access to the texts with similar passages that are stored locally on your hardware.